2018
DOI: 10.1001/jama.2018.12346
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory Medicare Bundled Payment Program for Lower Extremity Joint Replacement and Discharge to Institutional Postacute Care

Abstract: ClinicalTrials.gov Identifier: NCT03407885; American Economic Association Registry Identifier: AEARCTR-0002521.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
174
4
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(191 citation statements)
references
References 25 publications
11
174
4
2
Order By: Relevance
“…Prior single‐center studies of joint replacement under BPCI have suggested that savings accrue from reducing high‐cost institutional PAC care . Dummit et al found evidence of modest savings among BPCI participants compared to nonparticipants, as well as reduction in institutional PAC use and duration, and Finkelstein et al found similar patterns in CJR . CMS has released annual reports on BPCI performance, with similar findings for joint replacement .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Prior single‐center studies of joint replacement under BPCI have suggested that savings accrue from reducing high‐cost institutional PAC care . Dummit et al found evidence of modest savings among BPCI participants compared to nonparticipants, as well as reduction in institutional PAC use and duration, and Finkelstein et al found similar patterns in CJR . CMS has released annual reports on BPCI performance, with similar findings for joint replacement .…”
Section: Discussionmentioning
confidence: 90%
“…[4][5][6][7][8]29 Dummit et al found evidence of modest savings among BPCI participants compared to nonparticipants, as well as reduction in institutional PAC use and duration, 10 and Finkelstein et al found similar patterns in CJR. 3 CMS has released annual reports on BPCI performance, with similar findings for joint replacement. [11][12][13][14] The estimates from our work are qualitatively similar, though not identical, to previously published work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hip and knee replacements are the most common inpatient procedures performed for older Medicare beneficiaries (eg, >400 000 procedures in 2014) 1 and have been recently targeted by Medicare alternative payment models for improved quality and efficiency of care. [1][2][3] Although most patients are discharged home after hip and knee replacements (possibly with some form of home health care), about 30% are discharged to postacute care (PAC) facilities, most commonly skilled nursing facilities (SNFs), to help optimize functional recovery. 4 Postacute care practices after replacement procedures vary substantially [4][5][6][7] owing to lack of consensus on the optimal setting and intensity of PAC, and owing to different Medicare reimbursement approaches for alternative PAC.…”
Section: Introductionmentioning
confidence: 99%